Odyssey Self Reflection - Hotwheel / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
The design of the hot wheels inspired me to produce artworks which consist of drawing, painting, printmaking and sculpture. My artwork represented my childhood memories, where I would collect hot wheels and other toy cars. I would often base my artwork on some elements and principles which included repetition, size and various shapes. Other than considering both warm and cool colours to embellish my artwork, I also chose the amalgamation of media such as charcoal and soft pastel for my drawing.